Interplanetary shocks and the resulting geomagnetically induced currents at the equator. Issue 16 (25th August 2015) - Carter, B. A.; Yizengaw, E.; Pradipta, R.; Halford, A. J.; Norman, R.; Zhang, K.
Abstract: Geomagnetically induced currents (GICs) caused by interplanetary shocks represent a serious space weather threat to modern technological infrastructure. The arrival of interplanetary shocks drives magnetosphere and ionosphere current systems, which then induce electric currents at ground level. The impact of these currents at high latitudes has been extensively researched, but the magnetic equator has been largely overlooked. In this paper, we investigate the potential effects of interplanetary shocks on the equatorial region and demonstrate that their magnetic signature is amplified by the equatorial electrojet. This local amplification substantially increases the region's susceptibility to GICs. Importantly, this result applies to both geomagnetic storms and quiet periods and thus represents a paradigm shift in our understanding of adverse space weather impacts on technological infrastructure. Key Points: The d B /d t during sudden impulses is locally amplified by equatorial electrojet The d B /d t amplification occurs for both geomagnetic storms and quiet periods Power grid infrastructure in equatorial nations is likely to be affected